Design of complex emulsion interfaces for sugar reduction application - Elkwil, Omran (2019)
A low carbohydrate and free sugar diet is generally recommended by nutritionists and clinicians for losing weight, reducing risk of diabetes, cardiovascular diseases and metabolic syndrome. The aim of this research was to design complex emulsion interfaces for sugar reduction in emulsion-based food. A strategy was applied to evaluate whether O/W emulsions can be stabilised at a lower emulsifying starch content by utilising protein as co-emulsifier. It was hypothesised that oil-in-water (O/W) emulsions stabilised using octenyl succinic anhydride (OSA) starch do not require a closely packed starch layer at the interface for breakdown in the oral cavity by saliva α-amylase, also the interfacial starch can be reduced by utilising whey protein (WP) or sodium caseinate (NaCAS) as co-emulsifier a co-emulsifier when compared to using starch alone. If this emulsion was successfully stabilised with starch/protein mixed emulsifier, it can be developed into W1/O/W2 emulsion in which a highly concentrated sucrose solution can be encapsulated as a requirement of the taste enhancement approach. When the W1/O/W2 emulsion breaks down in the oral cavity and releases the sucrose, this will give consumer satisfaction in terms of sweet taste, without being a high carbohydrate-digestion product. By using this strategy, emulsion-based food products can be produced with an overall low carbohydrate content and whilst maintaining a satisfying level of sweet taste.